Genetic identification of residues involved in association of alpha and beta G-protein subunits. - Whiteway, M (1994)
The GPA1, STE4, and STE18 genes of Saccharomyces cerevisiae encode the alpha, beta, and gamma subunits, respectively, of a G protein involved in the mating response pathway. We have found that mutations G124D, W136G, W136R, and delta L138 and double mutations W136R L138F and W136G S151C of the Ste4 protein cause constitutive activation of the signaling pathway. The W136R L138F and W136G S151C mutant Ste4 proteins were tested in the two-hybrid protein association assay and found to be defective in association with the Gpa1 protein. A mutation at position E307 of the Gpa1 protein both suppresses the constitutive signaling phenotype of some mutant Ste4 proteins and allows the mutant alpha subunit to physically associate with a specific mutant G beta subunit. The mutation in the Gpa1 protein is adjacent to the hinge, or switch, region that is required for the conformational change which triggers subunit dissociation, but the mutation does not affect the interaction of the alpha subunit with the wild-type beta subunit. Yeast cells constructed to contain only the mutant alpha and beta subunits mate and respond to pheromones, although they exhibit partial induction of the pheromone response pathway. Because the ability of the modified G alpha subunit to suppress the Ste4 mutations is allele specific, it is likely that the residues defined by this analysis play a direct role in G-protein subunit association.